2018
DOI: 10.1137/16m1110042
|View full text |Cite
|
Sign up to set email alerts
|

Relating Graph Thickness to Planar Layers and Bend Complexity

Abstract: The thickness of a graph G = (V, E) with n vertices is the minimum number of planar subgraphs of G whose union is G. A polyline drawing of G in R 2 is a drawing Γ of G, where each vertex is mapped to a point and each edge is mapped to a polygonal chain. Bend and layer complexities are two important aesthetics of such a drawing. The bend complexity of Γ is the maximum number of bends per edge in Γ, and the layer complexity of Γ is the minimum integer r such that the set of polygonal chains in Γ can be partition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Durocher and Mondal [10] showed that every thickness-k graph can be drawn on k planar layers with bend complexity at most O(…”
Section: Related Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…Durocher and Mondal [10] showed that every thickness-k graph can be drawn on k planar layers with bend complexity at most O(…”
Section: Related Researchmentioning
confidence: 99%
“…We then color all the division vertices with a color different than the input colors. Durocher and Mondal [10] showed that if P i admits an b-bend uphill drawing on a point set S, then G i admits a O(b)-bend polyline drawing on S. Hence it suffices to consider only the simultaneous embedding of the spinal paths. Here we give a concise proof for completeness.…”
Section: Technical Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the arboricity of a graph G is the minimum number of forests needed to cover all edges of G, while G has thickness t if it is the union of t planar graphs. Durocher and Mondal [12] studied the interplay between the thickness t of a graph and the number of bends per edge in a drawing that can be partitioned into t planar sub-drawings.…”
Section: Introductionmentioning
confidence: 99%